Determination of calcium and sulfate species in aerosols associated with the conversion of its species through reaction processes in the atmosphere and its influence on cloud condensation nuclei activation. (15th February 2020) - Miyamoto, Chihiro; Sakata, Kohei; Yamakawa, Yoshiaki; Takahashi, Yoshio
Abstract: Calcium (Ca) species in aerosols collected in Higashi–Hiroshima in southwestern Japan were determined by X-ray absorption near-edge structure (XANES) analysis, and their size distributions and seasonal variation were investigated. Calcium K-edge XANES results showed that gypsum (CaSO4 ⋅2H2 O) and calcium oxalate (CaC2 O4 ⋅2H2 O) were the major Ca species that were formed by reactions of mineral particles in the atmosphere. These species exhibit similar hygroscopicity to that of calcite (CaCO3 ), which is an original Ca species in mineral particles. In addition, high hygroscopic Ca species, such as calcium nitrate [Ca(NO3 )2 ⋅4H2 O] and calcium chloride (CaCl2 ⋅2H2 O) were considered minor Ca species. Moreover, the formation of CaSO4 ⋅2H2 O by the reaction of mineral particles suppresses the formation of hygroscopic sulfate aerosol species, such as ammonium sulfate [(NH4 )2 SO4 ], reducing the number of cloud condensation nuclei (CCN). Sulfur K-edge XANES also confirmed that CaSO4 ⋅2H2 O was a major species of sulfate in coarse particles. By contrast, high hygroscopic sulfate, such as (NH4 )2 SO4, was major species in fine particle. In addition, CaSO4 ⋅2H2 O fraction to total sulfate increased during the sampling period, which was affected by a dust event. Consequently, the amount of hygroscopic sulfate in fine particles was decreased by the reaction, forming CaSO4 ⋅2H2 O in coarse particles in the presence of mineral dust. Although these facts have been indicated mostly by modeling and laboratory studies, the present research suggested that the reaction of CaCO3 to form CaSO4 ⋅2H2 O will reduce the amount of hygroscopic sulfate aerosols based on natural sample measurement in terms of the speciation of Ca and sulfate in aerosols using XANES spectroscopy. Highlights: Calcium (Ca) and sulfate chemical species in aerosol were revealed by XANES. The CCN activity of Ca and sulfate aerosols was discussed. The conversion of Ca minerals exerts a slight effect on enhancing CCN activity. The formation of low hygroscopic sulfate species reduces the number of CCN.